KUALITAS KEHIDUPAN DAN BATAS TERAPI - Piet Go (Litbang STFT Widya Sasana Malang, 2007)
“Quality of Life is increasingly used in many circles, especially in sociopolitical, medical, philosophical and theological sense, without clarifying the exact meaning, so that often it results in confusion. The Catholic Church especially during the Pontificate of Pope John Paul II (cfr.Evangelium vitae 23) gives a deepened meaning by involving the religious and spiritual dimension of man. So one cannot claim the right to die by invoking quality of life just in sociopolitical or medical sense. According to Pope Pius XII (1957) human life must be preserved, not at any cost with extraordinary means, but wirh ordinary means. In 1980 the Congregation for the Doctrine of the Faith did not reject that notion, but used and proprosed another term, namely “Proportionate and disproportionate”, since the first one (“Ordinary and extraordinary”) was misunderstandable, especially because of the progress in medical siences and technologies. So there are legitimate limits of therapy.